International Significance of Armenian Literature of the Golden Age - Dolukhanyan, Aelita (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Since the 18th century, when the Whiston brothers translated Moveses Khorenatsi’s “History of Armenia” into Latin, Armenian historiography has attracted the attention of European scholars. Saint-Martin played a great role in the process of the international recognition of Armenian studies, who in the two prefaces of the book «Mémoires historique et géographique sur l'Arménie» (1818) speaks admiringly about the historiography of the 5th century and the Armenian Middle Ages in general. According to him, the importance of Armenian historians is that when talking about ancient times, they usually paid more attention to the events they narrated, tried not to talk about events of little importance, and treated the style of their stories more carefully than Arab and Persian historians. The Armenian historiography of the Golden Age provides important information about the neighboring peoples: Persians, Greeks, Assyrians, Georgians, and Caucasian Albanians, often confirming this information by facts from other sources and archaeological excavations. Harlez, an important figure of the French Avestology, notes that with the facts brought by Moveses Khorenatsi and Yeghishe, it is possible to restore the lost parts of the “Avesta”, the sacred book of the Zoroastrian religion. Pavstos Buzand’s “History of Armenia” is a unique source on the history of the Arshakid dynasty of Persia and Armenia. It should not be forgotten that in the Middle Ages Agathangelos’ “History of Armenia” was translated into eight languages. Jean-Pierre Mahe, a prominent French Armenologist of our time, also makes a focus on the international value of Armenian historiography of the Golden Age.
Keywords: Philology